The Incidence of Contrast-Induced Nephropathy and the Need of Dialysis in Patients Receiving Angiography: A Systematic Review and Meta-Analysis - Wu, Mei-Yi; Lo, Wei-Cheng; Wu, Yun-Chun; Lin, Tsu-Chen; Lin, Chun-Hung; Wu, Mai-Szu; Tu, Yu-Kang (Frontiers in Medicine, 2022)
Objectives The risk of dialysis following contrast exposure is unclear. We aimed to examine the overall risk of contrast induced nephropathy and the need of dialysis based on a systematic review with random-effects meta-analysis. Methods We searched the electronic database including PubMed, Medline, Embase, and Cochrane Library from inception to 31 Oct, 2020 with predetermined search term to identify relevant studies. Observational studies investigating the association between contrast induced nephropathy after angiography and the need of dialysis were included, and summary risks were estimated. Two independent reviewers extracted the data, followed with random effects model to calculate the overall pooled incidence of contrast induced nephropathy and the need of dialysis after angiography. Subgroup-analysis and meta-regression were performed to assess heterogeneity of incidence across studies. Results Of 2,243 identified articles, 259 met our inclusion criteria were included in the meta-analysis after screening. Pooled effect estimates had the following summary incidence proportion for contrast induced nephropathy after angiography: 9.06% (95%CI: 8.53%-9.58%; derived from 120 studies) and 0.52% (95%CI: 0.37%-0.70%; derived from 110 studies) for the need of dialysis, respectively. The stratified summary incidence proportion of contrast induced nephropathy after contrast administration via intra-arterial route was 9.60% (95%CI: 9.0%-10.2%; derived from 106 studies) and was 0.6% (95%CI: 0.40%-0.80%; derived from 100 studies) for the need of dialysis, respectively. Our meta-regressions found that the amount of contrast medium exposure was associated with contrast-induced nephropathy. Conclusions The potential risk of dialysis needs to be communicated to patients undergoing procedures requiring contrast, especially via intra-arterial exposure.